FUNDAMENTAL WEB DESIGN: PENGENALAN DASAR MEMBUAT WEBSITE DENGAN HTML DAN CSS DI SMPN 3 PASAR KEMIS - Kurnianto Octian Junaidi; Afrizal Nur Perdana; Dony Sapta Nurhayadi; Priska Diniati; Yosef Ibrahim; Aditya Rangga Prasetya; Muhamad Fariz Rivai; Dzaky Azizan; Kecitaan Harefa (Shofanah Media Berkah, 2025)
Pelatihan